2020
DOI: 10.36525/sanitas.2019.15
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Giving Boiled Chicken Eggs And Papaya Fruit On The Improvement Of Hemoglobin Levels In Anemia Students

Abstract: Anemia in adolescent girls is quite high, the incidence of anemia nationally is 21.7%. Anemia in adolescents if left untreated will continue into adulthood and contribute greatly to AKI, premature babies, and low birth weight babies. One way to prevent this can be done by consuming boiled chicken eggs and papaya fruit. The purpose of this study was to determine the effect of boiled chicken eggs and papaya fruit on increasing Hb levels in anemic female students of SMP Negeri 22 Kerinci in2019. This type of rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…The differences in hemoglobin levels may be explained by differential intake of dietary iron during the menstrual period. Identical results were found in a study conducted by Susanti et al 28 that there was an effect of providing boiled chicken eggs and papaya to increase hemoglobin levels in female students. An earlier study reported that egg white protein was useful for recovery from iron deficiency anemia 18 .…”
Section: Discussionsupporting
confidence: 69%
“…The differences in hemoglobin levels may be explained by differential intake of dietary iron during the menstrual period. Identical results were found in a study conducted by Susanti et al 28 that there was an effect of providing boiled chicken eggs and papaya to increase hemoglobin levels in female students. An earlier study reported that egg white protein was useful for recovery from iron deficiency anemia 18 .…”
Section: Discussionsupporting
confidence: 69%
“…Zat besi merupakan mineral yang dibutuhkan tubuh untuk membentuk sel darah merah (hemoglobin). Sel darah merah mengandung hemoglobin yaitu protein yang membawa oksigen ke seluruh jaringan tubuh 7 . Ketika HB ada di dalam darah, tubuh tampak lemas, lelah, lesu, dan daya tahan tubuh melemah.…”
Section: Volumeunclassified
“…Data ini menunjukkan bahwa prevalensi anemia di Indonesia masih tinggi sehingga masih menjadi prioritas utama dalam perbaikan peningkatan gizi masyarakat. Prevalensi anemia paling banyak pada rentang usia 15 -24 tahun, kemudian disusul pada usia 25 sampai dengan 34 tahun 14 Papaya (Carica papaya L) merupakan buah yang banyak mengandung vitamin C yang berasal dari Amerika tropis. Buah pepaya merupakan buah yang digemari semua kalangan masyarakat, terutama dikonsumsi sebagai buah segar.…”
Section: Pendahuluanunclassified